Implementasi Pembelajaran Tajwid dan Sholat dengan Game Android di Sekolah Dasar Mursyidah Surabaya - Mubarokah, Arzaqillah (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2020)
The rapid advancement of technology has an impact on changes in various aspects, including education. The teaching and learning process does not only focus on using one or two manuals, but also integrates technological advances such as gadgets and internet connections. One of them is the use of educational android games by educators in the subject of Al-Quran Hadith (Qurdits) and Fiqh. The purpose of this study was to determine the perceptions of teachers and students on the application of the educational game titled Tajwid Adventure and fiqh game Marbel (Let's Learn) Prayer at SD Mursyidah Surabaya. In this study, the authors used qualitative methods, in order to describe the research in depth and in detail. Based on the results of the study, the authors concluded that the use of these two educational games provided many benefits to each party, especially for students, such as increased student interest in learning, learning in class was more communicative and fun and increased student learning outcomes. In addition, new challenges are also felt by teachers in the form of increasing the effectiveness of using educational android games and assisting students in choosing useful android gamesboth inside and outside the classroom